2007
DOI: 10.1080/03602550701575797
|View full text |Cite
|
Sign up to set email alerts
|

ModificationIn Situof EPDM Filled with Carbon Black by Glycidyl Methacrylate

Abstract: A method of chemical modification in situ of ethylenepropylene-diene rubber (EPDM) filled with carbon black was studied. A bifunctional monomer, glycidyl methacrylate (GMA), was used as the modifier to improve the dispersibility of carbon black in the rubber and to enhance the mechanical properties of EPDM vulcanizates. The effects of GMA on the structure and properties of EPDM vulcanizates such as determination of crosslinking density and vulcanizing properties as well as mechanical properties were investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…For the EMA‐GMA/CB composite, there is an increase in the torque with time after the time of 5 min, which can be attributed to reactions between the CB and EMA‐GMA copolymer. Jiang et al [ 40 ] reported that GMA, which contains epoxy groups, may react with active groups present in the surface of CB. According to the literature [ 12 ] different functional groups, such as carboxyls, hydroxyls, ketones among others, are present in the structure of CB.…”
Section: Resultsmentioning
confidence: 99%
“…For the EMA‐GMA/CB composite, there is an increase in the torque with time after the time of 5 min, which can be attributed to reactions between the CB and EMA‐GMA copolymer. Jiang et al [ 40 ] reported that GMA, which contains epoxy groups, may react with active groups present in the surface of CB. According to the literature [ 12 ] different functional groups, such as carboxyls, hydroxyls, ketones among others, are present in the structure of CB.…”
Section: Resultsmentioning
confidence: 99%